Integrasi Address Space Layout Randomization (ASLR) Pada Kernel Linux X86 (32bit) Untuk Mencegah Serangan Exploit Buffer Overflow - Rahman, Rakhmadi; Anugra, Ayu; Amin, Widyah Putri Auliya (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Buffer Overflow consist of two words, namely buffer and overflow. Buffer refers to area data storage, while overflow means overflowing. In simple terms, buffer overflow is a situation where the data storage are receives more data then its capacity. Buffer Overflow can also be interpreted as a frequently used method by hackers to exploit computer application systems. Buffer Overflow can damage the affected program. This is possible causing the program to not function properly, crash, or not at all can be run at all. Damage caused by buffer overflow can disrupts the operating system and causes irrecoverable data loss. Therefore, we must prevent buffer overflow exploit attacks, one of them the way we can do this i by implementing Addresss Space Layout Randomization (ASLR).